Frequency doubling by active in vivo motility of mechanosensory neurons in the mosquito ear. Issue 1 (10th January 2018) - Windmill, James F. C.; Jackson, Joseph C.; Pook, Victoria G.; Robert, Daniel
Abstract : Across vertebrate and invertebrate species, nonlinear active mechanisms are employed to increase the sensitivity and acuity of hearing. In mosquitoes, the antennal hearing organs are known to use active force feedback to enhance auditory acuity to female generated sounds. This sophisticated form of signal processing involves active nonlinear events that are proposed to rely on the motile properties of mechanoreceptor neurons. The fundamental physical mechanism for active auditory mechanics is theorized to rely on a synchronization of motile neurons, with a characteristic frequency doubling of the force generated by an ensemble of motile mechanoreceptors. There is however no direct biomechanical evidence at the mechanoreceptor level, hindering further understanding of the fundamental mechanisms of sensitive hearing. Here, using in situ and in vivo atomic force microscopy, we measure and characterize the mechanical response of mechanosensory neuron units during forced oscillations of the hearing organ. Mechanoreceptor responses exhibit the hallmark of nonlinear feedback for force generation, with movements at twice the stimulus frequency, associated with auditory amplification. Simultaneous electrophysiological recordings exhibit similar response features, notably a frequency doubling of the firing rate. This evidence points to the nature of the mechanism, whereby active hearing in mosquitoes emerges from the double-frequency response of the auditory neurons. These results open up the opportunity to directly investigate active cellular mechanics in auditory systems, and they also reveal a pathway to study the nanoscale biomechanics and its dynamics of cells beyond the sense of hearing.